Seasonal variation in hyaluronidase activity in seminal plasma of Murrah buffalo bulls in relation to seminal attributes and effect of thermal protection - MANDAL, D K; NAGPAUL, P K; MOHANTY, A K (The Indian Journal of Animal Sciences, 2014)
Study was conducted to find out the eifect of thermal stress ameluioration and seasonal variation on the hyaluronidase activity (HYA) in seminal plasma of Murrah buffalo bulls. Adult Murrah bulls (12) were divided in 2 equal groups and kept under different thermo-comfortable conditions. Body surface cooling in the experimental group was done by fanning (10 AM to 6 PM) and water sprinkiling 2-4 times during summer (April-June) and 2-times during rainy season (July- October) for 10 min each time. Overall mean (± sd) HYA in Murrah buffalo bulls seminal plasma was 5.04± 1.94 unit. Between experimental and control groups no significant variation in HYA was observed during summer (6,46±1.4vs 7.75±0.76) and rainy seasons (4.00±1.14 vs 5,46±0.56). Thermal stress amelioration had no significant effect on HYA of Murrah buffalo bulls semen, On overall basis hyaluronidase activity in seminal plasma was 7.10± 1.28, 4.73±1.14 and 3.29±0.98 during summer; rainy and winter seasons respectively and the differences were significant (P